2022
DOI: 10.1186/s12885-022-09601-5
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic trajectory of platelet counts after the first cycle of induction chemotherapy in AML patients

Abstract: Background Platelet counts varied over time after induction chemotherapy. We aimed to investigate the different trajectories of platelet counts after the first cycle of induction chemotherapy in patients newly diagnosed with acute myeloid leukemia. Methods and results In total, 149 individuals were included in this study. We identified four distinct trajectories using a group-based trajectory model: low- stability group (n = 27, 18.12%), low-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified the following errors in the article: The color in Fig. 1 was incorrectly marked and has been updated in this correction article.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified the following errors in the article: The color in Fig. 1 was incorrectly marked and has been updated in this correction article.…”
mentioning
confidence: 99%